Sex Differences in Resilience Factors and Emotional Health among Adolescents during Covid-19 - Sharma, Sailendra Kumar; Sharma, Narayan Prasad (Scientific Researches in Academia, 2024)
The most prolific pandemic of the 21st century has caused people throughout the world to be physically and psychologically affected. Numerous factors have influenced a cascade of stressful situations due to COVID-19. The responses to a stressful or traumatic situation may not only differ due to the resources available to them, their personalities, and the level of exposure. It can also be dependent upon the biological sex of the individual. A survey was conducted for adolescents between the ages of 12-19 years where n = 74 males and n = 108 females. The data was collected during the first wave of the pandemic. The study was conducted to explore the Resilience Factors (RF) and their relationship with Emotional Health (EH); the calculation of levels of variables associated with RF and the levels of EH. Sex differences in RF and EH were also tested to assess their differences. The current study found that there were no significant differences between male and female adolescents in any RF. There were but significant differences in EH between them with males having higher levels than females. Individuals with high resilience are less likely to be affected than those with low resilience by the effect of ‘stress exposure' symptoms of depression mediated by anxiety which results in better EH.